2011
DOI: 10.1007/s10545-011-9284-x
|View full text |Cite
|
Sign up to set email alerts
|

Transition of young adults with phenylketonuria from pediatric to adult care

Abstract: Transition of patients with PKU from pediatric to adult care seems to be successful in Leipzig. Patients were mostly satisfied with the transition situation. Still, some suggestions for improvements appeared to be desirable. During transition medical care and metabolic control were stable. However, with regard to psychosocial and socioeconomic data differences to the control population were detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 42 publications
(50 reference statements)
2
42
0
11
Order By: Relevance
“…27,28,29,30,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98 Psychiatric and executive function impairments such as attention and processing-speed deficits, 73,77,80 behavioral and emotional problems, 81 psychiatric disorders, 73,81 and cognitive deficits 73,81,82,83 may have an overall negative effect on the individual's quality of life. If an adult is not followed by a metabolic clinic, he or she may not know that diet treatment is now recommended for life or that new treatment options are available that may make adherence more attainable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28,29,30,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98 Psychiatric and executive function impairments such as attention and processing-speed deficits, 73,77,80 behavioral and emotional problems, 81 psychiatric disorders, 73,81 and cognitive deficits 73,81,82,83 may have an overall negative effect on the individual's quality of life. If an adult is not followed by a metabolic clinic, he or she may not know that diet treatment is now recommended for life or that new treatment options are available that may make adherence more attainable.…”
Section: Discussionmentioning
confidence: 99%
“…Familial, 84,85,88,89,90 social, 27,91,92 and health-care provider support systems 27,30,85 are important to assist individuals with pursuing treatment for PKU. 85,86,87 Distance to the metabolic clinic, lack of transportation, and inability to get time off work have also been cited as reasons for not accessing treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies that provided comparative German census data did report differences in educational attainment between subjects with PKU and the general population. In the first study, patients with PKU, 96% of whom were on a restricted diet, achieved lower levels of academic achievement, specifically for graduation at senior high school level, compared with the general population . The second study found that educational attainment was only lower in patients with PKU whose treatment was interrupted (for at least 4 years starting at the age of 7‐14 years), while patients who had been continuously treated until the end of adolescence demonstrated comparable education status to the census population .…”
Section: Social Outcomesmentioning
confidence: 98%
“…Several studies used standardized QoL tests, which reported good QoL in patients, comparable with that of healthy controls . However, specific QoL domains may be affected in adults with PKU, despite normal scores overall.…”
Section: Quality Of Lifementioning
confidence: 99%